The problem of objectivity in images of nature: Von Humboldt and Goethe - Gutiérrez García, Rosa (Escritura e Imagen, 2021)
This study aims to problematise the notion of objectivity in the images of nature through Von Humbold and Goethe, in the debate on scientific representation and through the relationship between science and art. To this end, this essay has been divided into two distinct parts. The first exposes a state of the question about the parameters used around the idea of objectivity, both in the scientific and the philosophical context, exposing the pictorial antecedents that will give way to the second part of this essay, and the way in which these ideas are elucidated in the particular cases of von Humboldt and Goethe.
Keywords: objectivity; representation; views of nature; landscape; truth; art; science